Hypersensitive response and pathogenicity gene based molecular detection of Xanthomonas campestris pv. campestris causing black rot disease in cabbage - DINESH SINGH, B.T. RAGHAVENDRA* and (Indian Phytopathology, 2016)
Xanthomonas campestris pv. campestris is a seed borne pathogen that causes black rot disease in cabbage. The development of a rapid and sensitive detection method for Xanthomonas campestris pv. campestris in cabbage seeds and plants is essential for high-throughput certification purpose. A PCR-based method has been developed for the rapid and sensitive detection of the X. campestris pv. campestris. A pair of oligos was designed specifically amplify a 768 bp of the hrpF gene from X. campestris pv. campestris. Under stringent conditions of amplification, a PCR product of 768 bp of the hrpF was obtained from the X. campestris pv. campestris. Specificity of the oligos was checked with the DNA of X. oryzae pv. oryzae, Ralstonia solanacearum, Pseudomonas fluorescens and Bacillus subtilis wherein, the amplification was observed only in X. campestris pv. campestris. The primer was highly sensitive and was able to detect up to 0.5ng/Âµl bacterial DNA present in the master mix. BIO-PCR protocol was developed for detecting the pathogen from artificially contaminated seed samples. The primer was sensitive enough to detect up to 0.01% of X. campestris pv. campestris contaminated seed sample by employing BIO-PCR assay.